Strategic identification of flash flood risks in malaysian construction: Integrating stakeholder perspectives for enhanced resilience in pre-construction and construction phases - Mohammad Syamsyul Hairi, Saad; Mohamad Idris, Ali; Putri Zulaiha, Razi; Noram Irwan, Ramli; Doh, Shu Ing (Penerbit UMP, 2025)
The Malaysian construction industry faces escalating challenges from flash floods, exacerbated by rapid urbanization and climate change. While geographic and infrastructural vulnerabilities are well-researched, a critical gap exists in understanding how construction-phase activities contribute to flood risks. This study addresses this gap by systematically identifying flash flood risks associated with the pre-construction and construction phases, offering industry professionals and policymakers actionable insights. Through semi-structured interviews with 29 key stakeholders, including project managers, engineers, and public authorities, this study applies thematic analysis to uncover three primary risk categories: (1) location risks, including inadequate stormwater management and topographic challenges, (2) pre-construction risks, such as project scale, site location, and offsite impacts, and (3) construction-phase risks, particularly poor scheduling, and failure to implement best management practices. The findings highlight that insufficient planning and mitigation during construction significantly heighten flood vulnerabilities, yet these factors are often overlooked in current practice. To address these challenges, this research proposes a comprehensive framework for integrating flood risk management into construction project planning and execution. Key recommendations include using sustainable construction techniques, such as permeable surfaces, bio-retention ponds, detention ponds, silt fences, and green infrastructure. For policymakers, the study calls for updated regulatory guidelines to enforce stricter flood resilience measures in construction projects. Through targeted solutions for industry experts and policymakers, this research strengthens Malaysia's construction industry, enabling safer, more sustainable growth in flood-prone areas.